Dynamic Contrast–Enhanced Magnetic Resonance Imaging in Patients with Pulmonary Arterial Hypertension. (1st March 2014) - Swift, Andrew J.; Telfer, Adam; Rajaram, Smitha; Condliffe, Robin; Marshall, Helen; Capener, Dave; Hurdman, Judith; Elliot, Charlie; Kiely, David G.; Wild, Jim M.
Abstract : Dynamic contrast–enhanced (DCE) time‐resolved magnetic resonance (MR) imaging is a technique whereby the passage of an intravenous contrast bolus can be tracked through the pulmonary vascular system. The aim of this study was to investigate the prognostic significance of DCE‐MR pulmonary blood transit times in patients with pulmonary arterial hypertension (PAH). Seventy‐nine patients diagnosed with PAH underwent pulmonary DCE imaging at 1.5 T using a time‐resolved three‐dimensional spoiled gradient echo sequence. The prognostic significance of two DCE parameters, full width at half maximum (FWHM) of the first‐pass clearance curve and pulmonary transit time (PTT), along with demographic and invasive catheter measurements, was evaluated by univariate and bivariate Cox proportional hazards regression and Kaplan‐Meier analysis. DCE‐MR transit times were most closely correlated with cardiac index (CI) and pulmonary vascular resistance index (PVRI) and were both found to be accurate for detecting reduced CI (FWHM area under the curve [AUC] at receiver operating characteristic analysis = 0.91 and PTT AUC = 0.92, respectively) and for detecting elevated PVRI (FWHM AUC = 0.88 and PTT AUC = 0.84, respectively). During the follow‐up period, 25 patients died. Patients with longer measurements of FWHM ( P = 0.0014) and PTT ( P = 0.004) were associated with poor outcome at Kaplan‐Meier analysis, and both parameters were strong predictors of adverse outcome from Cox proportional hazards analysis ( P = 0.013 and 0.010, respectively). At bivariate analysis, DCE measurements predicted mortality independent of age, gender, and World Health Organization functional class; however, invasive hemodynamic indexes CI, PVRI, and DCE measurements were not independent of one another. In conclusion, DCE‐MR transit times predict mortality in patients with PAH and are closely associated with clinical gold standards CI and PVRI.